Britten's Acoustic Miracles in Noye's Fludde and Curlew River - Swanson, Cole. (2017)
Abstract: Benjamin Britten sought to engage the English musical public through the creation of new theatrical genres that renewed, rather than simply reused, historical frameworks and religious gestures. I argue that Britten's process in creating these genres and their representative works denotes an operation of theatrical and musical "re-enchantment," returning spiritual and aesthetic resonance to the cultural relics of a shared British heritage. My study focuses particularly on how this process of renewal further enabled Britten to engage with the state of amateur and communal music participation in post-war England. His new, genre-bending works that I engage with represent conscious attempts to provide greater opportunities for amateur performance, as well cultivating sonically and thematically inclusive sound worlds. As such, Noye's Fludde (1958) was designed as a means to revive the musical past while immersing the Aldeburgh Festival community in present musical performance through Anglican hymn singing. Curlew River (1964) stages a cultural encounter between the medieval past and the Japanese Nō theatre tradition, creating an atmosphere of sensory ritual that encourages sustained and empathetic listening. To explore these genre-bending works, this thesis considers how these musical and theatrical gestures to the past are reactions to the post-war revivalist environment as well as expressions of Britten's own musical ethics and frustrations. The thesis concludes by considering how Britten's own works are revived as theatrical devices in Wes Anderson's film Moonrise Kingdom (2012).; Thesis (M.A.)--Tufts University, 2017.; Submitted to the Dept. of Music.; Advisor: Alessandra Campana.; Committee: Joseph Auner, and Philip Rupprecht.; Keywords: Music, and Theater.